Mengenalkan Emosi dengan Emoji Menggunakan Media Flash Card pada Anak Usia Dini di UPT PPRSA Inang Matutu Makassar - Eka Sufartianinsih Jafar; Nirmayanti Nirmayanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2022)
Abstract: Introducing Emotions with Emoji Using Flash Card Media in Early Childhood at UPT PPRSA Inang Matutu Makassar. This study aims to use flash card media to introduce emotions with pictures of emojis to early childhood at UPT PPRSA Inang Matutu. The method of implementing this activity is carried out in five stages, namely conducting needs analysis, preparation, making flash cards, implementing activities and evaluating the results of activities in the form of observations. The observations showed that in the first step, some of the children already knew the emotions shown from the emojis, although some were still shy and kept silent for a long time before mentioning the emotions. In the second step, all the children were able to point out the type of expression they meant, although some were still pointing the wrong way. In the third step, the children were very active in expressing their emotions and following the emotions in the emojis, although some children were still lacking in expressing their emotions.